Creation of Integrated Problem-Based Learning Electronic Student Worksheets to Improve Problem-Solving Skills Vocational School Students - Philiani, Suci (PILLAR OF PHYSICS EDUCATION, 2025)
The rapid advancement of science and technology requires skills such as solving complex problems known as 21st century skills. According to the information collected from this study, the students' problem-solving skills are low. The solution that can be done to improve this problem-solving ability is to create teaching materials in the form of electronic student worksheets integrated with problem-based learning. This research aims to develop and determine the feasibility and practicality of electronic student worksheets. This research method employs the Dick and Carey model, which consists of nine stages: identifying needs to determine objectives, analyzing learning tasks, examining learner characteristics and learning contexts, formulating specific learning objectives, creating assessment instruments, developing learning strategies, selecting and developing teaching materials, designing and implementing formative evaluations, and conducting revisions. The instrument used was the learners' problem solving ability needs sheet which was filled in by 24 learners.  The results of the validation test were obtained with very valid criteria at a value of 0.93. The results of the practicality test were obtained with a fairly practical criterion of a value of 0.74. So it can be concluded that electronic student worksheets integrated problem-based learning to improve the problem-solving ability of vocational school students is valid and practical to use.